Going to university: considerations for students with diabetes. (30th November 2020) - Dalton, Jo; Poole, Ruth
Abstract : The majority of students attending UK university for the first time are in their late teens or early 20s. 1 This age has been described as emerging adulthood and characterised by the ability to accept responsibility for oneself, make independent decisions and become financially independent. 2 This is considered a vulnerable time for people with diabetes and the need for uninterrupted, coordinated, flexible, comprehensive and accessible care is recognised. 3, 4 Many groups have looked at the challenges of transition from paediatric to adult care 4, 5 but there exists very little data on the specific challenges of university for students with diabetes. 6